Kritisk romantik - om opfattelsen af den danske guldalder I ANLEDNING AF EN DISPUTATS OM N.L.HØYEN - Vammen, Hans (Historisk Tidsskrift, 1987)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The article takes up the question of where the Danish »Golden Age« should be located in the context of the history of ideas and how it should be chronlogically delimited. Combining traditional approaches from the fields of Danish literary and historical research, it argues that a definite set of critico-romantic ideas dominated Danish culture and politics from 1799 to 1838. The Kantian Critique was combined with a loftier, overall view of nature and history, recognized through religion, science and art in the Piatonic triad of the good, the true and the beautiful. It is a view that resembles those of Leopold von Ranke, the brothers Humboldt and the elder Goethe in Germany, but it is not copied from them. Its protagonists were a group of natural scientists and humanists, headed by the physicist, H. C. Ørsted, his brother A. S. Ørsted, who combined legal scholarship with pre-eminent political office, the philosopher, F. C. Sibbern, and the theologian, J. P. Mynster. These same critico-romantic ideas were also predominant in literature (the Oehlenschlæger Circle) and public administration (Jonas Collin).